A Replication of "When a Doctor Falls from the Sky: The Impact of Easing Doctor Supply Constraints on Mortality", Okeke E.N. (2023) - Emma McManus; Joseph Richardson; Vasudha Wattal; Ritchie Woodard (Institute for Replication (I4R), 2023)
Okeke (2023) evaluates a policy experiment conducted in Nigeria, whereby communities were randomly allocated to receive a new doctor at the local public health center. The performance of these centers was compared to other sites which were allocated either a new midlevel health-care provider, or no additional staff. The study finds that communities assigned a new doctor were associated with a decrease in seven-day infant mortality, such a decrease was not observed in communities assigned a midlevel health-care provider. This suggests that it is the 'quality' of the additional doctor driving the effects rather than due to a quantity increase of an additional health worker. The size of the mortality reduction increased with increased exposure to the intervention. We first conduct a computational reproduction, rerunning the original code and data, finding that the results reported in the original study are reproducible. Second, we test the robustness of the results in several ways, by 1) adapting the existing controls to make the results robust to contamination bias, 2) altering and adding to the control variables included, 3) changing the specification or regression technique used, and 4) testing coding grouping and changing how service use was coded. These changes cause little change to the point estimates, although we find that the original paper's standard errors were overly conservative, and thus the statistical significance of some results was understated.
Keywords: 330